Nursing care for patients with rare diseases on the example of patients with Alternating Hemiplegia of Childhood - Pazdur, Małgorzata (Health Promotion & Physical Activity, 2019)
Introduction: Rare diseases are those which occur in 1 person in 2000. Usually they are genetically conditioned. They also comprise diseases which appear as a result of metabolic, immunological defects, infections and uncommon cancers. Development of science, especially genetics prompted discovery of new gene’s mutations. One of them is a mutation of ATP1A3 which alternating hemiplegia of childhood. It is a disease whose manifestations appear in early childhood and are unpredictable. Strokes can be hemiplegic or tetraplegic. Sometimes they are accompanied by problems with swallowing and breathing. The aim of the thesis was to compare 2 different cases of patients suffering from AHC, to show problems connected with taking care of them in bio-psycho-socio-spiritual dimensions and to present a model of care on the example of Dorothey Orem’s theory. Material and methods: The comparative method used in the work compares two cases of patients. It is a quality work. Techniques of interview, observation, measurement and documentation analysis were also applied. An interview questionnaire containing 13 questions and an observation conducted in everyday circumstances made it possible to show care problems of patients with AHC. The research was carried out from March 2018 to May 2018. Two cases were juxtaposed: a 10-year-old girl and a 34-year-old man. Results and conclusions: Patients who suffer from rare diseases have restricted access to diagnosis, cure, rehabilitation and social assistance. They often grapple with lack of understanding on the part of society and medical staff who do not have enough knowledge about this issue. By comparing 2 cases it was proved that care problems of these patients are very complicated and vary depending on age, type of stroke, intensity, duration of the disease and family’s and society’s support. The care system of Dorothey Orem seems to be the best one.